Australian women with good financial knowledge fare better in divorce. Issue 2 (May 2022) - West, Tracey; Mitchell, Elizabeth
Divorce dissolves couple households, who likely specialised in household financial decision-making tasks, into singles who need to learn new skills. Financial decisions will be particularly challenging for those newly separated people that are lacking knowledge and confidence. Given the substantive literature supporting the lack of financial knowledge of women in comparison to men, women are likely to be more disadvantaged by this aspect of divorce. We employ the HILDA Survey and find support for the role of financial literacy in improving wealth outcomes in divorce, particularly for women. We find that the positive impact is significant over the long term. This research contributes to knowledge of the role of financial education in building resilience to endure financial shocks. JEL classification:D14; G53; G50; J12; J16